Health Promotion Plan at the Basic Health Unit of Forte São João in Vitória - ES - Herrera, Cassius (2023)
The article analyzes the fundamental role of Basic Health Units in promoting the health of the Forte São João community in Vitória, Espírito Santo. Throughout its history, dating back to 1592, this area has faced challenges such as limited access to services and poor housing conditions. Based on data from the Municipal Health Secretary and information collected at the local Basic Health Unit, the study identified coronavirus infection as one of the main health problems across all age groups, along with other infectious and chronic diseases. Age-specific analysis revealed that different groups faced specific health challenges. The main demands of the Basic Health Unit included cases of coronavirus infection, hypertension, diabetes, routine consultations, and general exams. The study concluded that Forte São João faces significant challenges due to poor housing conditions, low education levels, limited access to medical care, and high crime rates. However, it highlighted the vital role of Basic Health Units in improving the quality of life and comprehensive well-being of the community. These units play a crucial role in prevention, health education, and promoting healthy lifestyles. There is a need for health policies aimed at meeting the specific needs of this community and improving their quality of life.